The emergence of American amphibious warfare, 1898-1945 - Nasca, David S., 1979- (Studies in naval history and sea power, 2020)
"The Emergence of American Amphibious Warfare, 1898-1945 examines how the United States became a superpower through amphibious operations in order to project military power. While other major world powers pursued and embraced different weapons and technologies in order to create different means of waging war, the United States was one of the few countries that spent decades training, developing, and employing amphibious warfare to pursue its national interests"--